Author Correction: Active Printed Materials for Complex Self-Evolving Deformations. Issue 1 (December 2018) - Raviv, Dan; Zhao, Wei; McKnelly, Carrie; Papadopoulou, Athina; Kadambi, Achuta; Shi, Boxin; Hirsch, Shai; Dikovsky, Daniel; Zyracki, Michael; Olguin, Carlos; Raskar, Ramesh; Tibbits, Skylar
A correction has been published and is appended to both the HTML and PDF versions of this paper. The error has not been fixed in the paper